New Living Cases on Corporate Governance - Hilb, Martin (Management for Professionals,, 2021)
This unique open access book features a selection of Living Cases on Corporate Governance, which were developed and compiled by chairpersons, members of the board of directors, and CEOs in various countries, working in close collaboration with prominent researchers. Each Living Case addresses a current issue that a given company or institution needs to resolve. For every Case, the goal is formulated by the researcher, in consultation with the client. The participants of internal or external board seminars, or university students, then work in teams to analyze the problem, develop an innovative and feasible solution, and summarize the most important lessons learned. .